LINGUISTIC LANDSCAPE PORTRAYED IN INDONESIAN EFL TEXTBOOKS: A DESCRIPTIVE STUDY - Kharisma, Adib Jasni; Ginting, Pirman; Hasnah, Yenni; Utomo, Muhammad Ikhsan (Jurnal As-Salam, 2023)
This research examines the linguistic landscape within 4 (four) English as a Foreign Language (EFL) textbooks in Indonesia, employing Cenoz and Gorter’s theoretical framework. The primary objectives of this study are to categorize the various linguistic landscape elements present in Indonesian EFL textbooks and provide a comprehensive description of the characteristics of these linguistic landscapes. The analysis was conducted through a descriptive qualitative methodology, focusing on linguistic landscape items within EFL textbooks used in Grades I, II, IV, and V, comprising a total of 116 images. These items encompassed monolingual, bilingual, and multilingual components. Specifically, 100 images featured English-only elements, establishing English as the dominant language in these instances, while 3 images were exclusively in Bahasa Indonesia, 1 in Arabic, and 12 incorporated both English and Indonesian. Including these linguistic elements is intended to familiarize students with English sentence structures in the textbooks, as English holds a prominent status as an international language.